Proses Komunikasi Pelaksanaan Program Satu Milyar Satu Kecamatan Di Provinsi Jambi - Siti Kurniasih; Djuara P Lubis; Basita Ginting (Institut Pertanian Bogor, 2014)
AbstractThe aims of this research are to describe the communication process in Samisake program of provincial level up to the village level and to analyze the communication process in Samisake program at village level. This research was conducted in November-December 2013, to two districts, namely Muaro Sebo Ulu district and Jelutung district. Total of respondents were 65 people. Hypothesis test used Spearman Rank Correlation.The results showed that the communication process in Samisake program from the province to the village was conducted by holding meetings of coordination between Regional and District. This meeting were led directly by the Governor. Credibilityfacilitator in Maro Sebo Ulu and Jelutung classified as high. While respondent’s participation in Samisake Program at Maro Sebo Ulu and Jelutung were high. Credibility facilitators are very significantly related with participation’s requirements. Based on t-test procedure, there was no significant differences between Maro Sebo Ulu anda Jelutung districts.Keywords: communication process, Samisake program, house improvement